2022
DOI: 10.3389/fcell.2022.834561
|View full text |Cite
|
Sign up to set email alerts
|

Rnd3 Expression is Necessary to Maintain Mitochondrial Homeostasis but Dispensable for Autophagy

Abstract: Autophagy is a highly conserved process that mediates the targeting and degradation of intracellular components to lysosomes, contributing to the maintenance of cellular homeostasis and to obtaining energy, which ensures viability under stress conditions. Therefore, autophagy defects are common to different neurodegenerative disorders. Rnd3 belongs to the family of Rho GTPases, involved in the regulation of actin cytoskeleton dynamics and important in the modulation of cellular processes such as migration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We also noted expression selectively in LC-NE neurons of a number of genes whose expression is altered in animal models or in human disease in the LC (SSTR2, PHOX2A, PHOX2A) [45,46]. We identified LC enrichment of a number of genes that have been associated at the cellular level with apoptosis, cell loss, or pathology in the context of neurodegeneration (RND3, P2RY1) [47][48][49][50]. We also noted enrichment of NT5DC2 in LC, a gene which has been associated with attention-deficit hyperactivity disorder (ADHD) and regulates catecholamine synthesis in vitro [51,52].…”
Section: Discussionmentioning
confidence: 91%
“…We also noted expression selectively in LC-NE neurons of a number of genes whose expression is altered in animal models or in human disease in the LC (SSTR2, PHOX2A, PHOX2A) [45,46]. We identified LC enrichment of a number of genes that have been associated at the cellular level with apoptosis, cell loss, or pathology in the context of neurodegeneration (RND3, P2RY1) [47][48][49][50]. We also noted enrichment of NT5DC2 in LC, a gene which has been associated with attention-deficit hyperactivity disorder (ADHD) and regulates catecholamine synthesis in vitro [51,52].…”
Section: Discussionmentioning
confidence: 91%
“…We also noted expression selectively in LC-NE neurons of a number of genes whose expression is altered in animal models or in human disease in the LC ( SSTR2 , PHOX2A , PHOX2B ) ( Fan et al, 2018 ; Ádori et al, 2015 ). We identified LC enrichment of a number of genes that have been associated at the cellular level with apoptosis, cell loss, or pathology in the context of neurodegeneration ( RND3 , P2RY1 ) ( Pietrowski et al, 2021 ; Moore et al, 2000 ; Cueto-Ureña et al, 2022 ; Dong et al, 2021 ). We also noted enrichment of NT5DC2 in the LC, a gene which has been associated with ADHD and regulates catecholamine synthesis in vitro ( van Hulzen et al, 2017 ; Nakashima et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have identified RND3 as a protective factor for mitochondrial function; indeed, the absence of RND3 activity has been related with altered mitochondria oxidative metabolism, favoring dependence of cells on glycolysis to obtain energy [42,43]. In other cellular models, the absence of RND3 has been related with an increase of ROS generation and mitochondria dysfunction; moreover, a physical interaction between PPARγ and RND3 has been described to potentiate mitochondrial function [44].…”
Section: Discussionmentioning
confidence: 99%